The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0103-65132013005000068
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação de métodos multicritério ao problema de escolha de modelos de pagamento eletrônico por cartão de crédito

Abstract: É crescente o uso de meios de pagamentos eletrônicos no sistema econômico. Este trabalho realiza um estudo que compara os resultados da aplicação de diferentes métodos de apoio multicritério à decisão (AMD) à avaliação das três tecnologias de pagamento eletrônico mais comumente utilizadas no Brasil. Para isso utiliza-se um conjunto de métodos: THOR (S1, S2 e S3), ELECTRE (I e II) e PROMETHÉE II. Os resultados da modelagem indicaram que não há uma prevalência significativa de uma alternativa, ou seja, uma tecno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
4
Order By: Relevance
“…Among its main contributions, we emphasize the application of the THOR multi-criteria system in waste recycling in Brazil 20 and in processes associated with health 22 . Gomes and Costa 18 applied this method, together with the METHODS ELECTRE (I and II) and PROMETHÉE II, to the problem of choosing electronic payment models by credit card, and other authors used it to establish strategies for the purchase of a frigate opportunity for the Brazilian Navy 25 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among its main contributions, we emphasize the application of the THOR multi-criteria system in waste recycling in Brazil 20 and in processes associated with health 22 . Gomes and Costa 18 applied this method, together with the METHODS ELECTRE (I and II) and PROMETHÉE II, to the problem of choosing electronic payment models by credit card, and other authors used it to establish strategies for the purchase of a frigate opportunity for the Brazilian Navy 25 .…”
Section: Methodsmentioning
confidence: 99%
“…The THOR method is based on three axiomatic concepts/theories for simultaneous use: preference modeling (approaching the French school -non-compensatory model), multi-attribute utility theory (bringing it closer to the American school -compensatory model) and theories that deal with inaccurate information. The combination of these theories allows quantifying the attractiveness of each alternative by creating a non-transitive aggregation function 18 . The use of THOR allows a faster and more efficient analysis of alternatives, considering the non-determinism of the weight assignment process, and quantifying this non-determinism, reapplying it in the process of ordering the alternatives 19 .…”
Section: Brazilian Navy Ship Of Hopementioning
confidence: 99%
See 1 more Smart Citation
“…As with the conclusions of Gomes & Costa (2015) it is here pointed out that the decision maker should consider a different method solution to enhance his decision process for greater knowledge of the problem.…”
Section: Ranking Initial Ranking Electre III Saw Topsis Promethee Ii mentioning
confidence: 94%
“…Moshkovich et al (2012) evaluated the stability of the results obtained through the SAW and TODIM methods. Gomes & Costa (2015) used a set of methods, including ELECTRE I, II and PROMETHEE II, in order to evaluate the differences between the rankings generated by these different methods in the choice of an electronic payment system. In turn, Yoon & Hwang (1995, p.68) suggested that MCDM ranking methods should be evaluated in the sense of predicting the initial rankings given by the decision maker, that is "how well a method predicts unaided decisions made independently of the judgments used to fit the model".…”
Section: Introductionmentioning
confidence: 99%